Skyhigh Enterprise: Titan Straps / Fatin Nurazhanis Muhd Salleh ...[et al.] - Muhd Salleh, Fatin Nurazhanis; Razaman, Fatin Nuranisah; Ismail, Emija; Mohamad, Nur Alisya Amani; Md Zin, Nur Arisha (2017)
Our business is established based on the high rates of accidents during hiking activities, construction works and others among consumer nowadays, and the high price for the best quality of the tools affect the consumers to find the convenient yet reasonable and affordable. We come out with the idea to ease their ways at appropriate range of prices. There are a few reasons why we choose this particular business. The first reason is we want everybody to feel safe of using our straps while doing their works at appropriate range of prices. The second reason is we want to offer the customers convenient way without require any extra cost, feel safe during hiking, constructing, gardening and etc as we highlighted the safeness.